APPLICATION OF STATISTICAL MODELS TO THE COLLABORATIVE PUBLICATIONS DATA IN THEORETICAL POPULATION GENETICS - Gupta, B.M.; Karisiddappa, C.R. (Malaysian Journal of Library and Information Science, 2000)
Studies the growth and proportion of different types of co-authored publications in theoretical population genetics. Explores the applicability of appropriate statistical model to the decline in the proportion of single-authored publication with time. Studies the applicability of selected statistical models to the distribution of authorship in publications of theoretical population genetics with time.